PENGARUH CITRA PERUSAHAAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KENTUCKY FRIED CHICKEN (STUDY PADA KENTUCKY FRIED CHICKEN METROPOLITAN CITY PEKANBARU) - Dian Rahmadini; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at Kentucky Fried Chicken Metropoltan City Pekanbaru, located on Jalan Soebrantas Panam. The problem in this research is the decrease in the number of purchases, the percentage of achievement of the transaction target per year has decreased, and not achieving the target number of transactions per year, this is thought to be influenced by a decrease in consumer purchasing decisions. The purpose of this study was to determine the effect of company image and product quality on purchasing decisions on Kentucky Fried Chicken. In this research the method used is quantitative descriptive with SPSS program. The population in this study are consumers of Kentucky Fried Chicken. Samples were taken based on the method using the Slovin formula, amounting to 100 respondents. Hypothesis testing uses simple linear analysis and multiple linear analysis with the results showing that the company's image and product quality significantly influence Kentucky Fried Chicken's purchasing decisions. With the calculation of the coefficient of determination (R2) simple company image of the purchase decision obtained an R square value of 0.560 or 56% and product quality on the purchase decision obtained an R square value of 0.687 or 68.7%. Calculation of multiple determinations of company image and product quality on purchasing decisions obtained an R value of 0.731. This shows that the percentage contribution of the influence of corporate image variables and product quality on purchasing decisions by 73.1% while the remaining percentage of 26.9% is influenced by other variables not included in this research variable. Keywords: Company Image, Product Quality, Purchasing Decisions